Risks in US bank international exposures - Nicola Cetorelli; Linda Goldberg (Federal Reserve Bank of New York, 2006)
U.S. banks have substantial exposure to foreign markets such as Europe and Latin America. In this paper, we show how the amounts and forms of these exposures have evolved over time and note the changes in embodied risks taken through banks' crossborder activity, local claims, and derivative positions. Our findings vary with the type of U.S. bank. Compared with other banks, money-center banks tend to have a greater share of their assets in foreign exposures. Some of money-center banks' exposure to riskier countries, particularly Latin American countries, is achieved through the activities of local branches and subsidiaries that take on liabilities as well as assets, a strategy that reduces their bank transfer risk accordingly. As a share of total international exposures, the transfer risk assumed by money-center banks tends to be significantly lower than that of other banks.
Keywords: F3; G2; 330; bank; foreign exposure; cross border; lending; capital; claims; derivatives; business cycle; interest rates; Internationale Bank; Bankrisiko; Internationale Finanzierung; USA; Welt